Does a blue crab putative insulin-like peptide binding protein (ILPBP) play a role in a virus infection?. (November 2016) - Huang, Xiaoshuai; Bae, Sun-Hye; Bachvaroff, Tsvetan R.; Schott, Eric J.; Ye, Haihui; Chung, J. Sook
Abstract: Insulin-like peptides (ILPs) have regulatory roles in reproduction, development and metabolism in invertebrates. The mode of ILP actions has not been well studied in invertebrates in regard to the role of binding partners, i.e., ILP binding protein (ILPBP). In this study, the full-length cDNA of Callinectes sapidus ILPBP ( Cas-ILPBP, 960 bp) has been isolated using RACE cloning, having short 5′ and 3′ UTRs of 30 and 162 bp, respectively. The predicted precursor of Cas-ILPBP (255 aa) contains, in order a signal peptide (23 aa), an insulin-like growth factor (IGF) binding (IB) domain (79 aa), a kazal-type serine protease inhibitor (KI) domain (36 aa) and an immunoglobulin (Ig) domain (101 aa). Phylogenetic analysis shows that Cas-ILPBP is grouped with the ILPBPs of other crustacean species, and it shares the closest relationship with the ILPBP from another crab species, Scylla paramamosain . Transcripts of Cas-ILPBP are found in all examined tissues, with the highest levels in the nervous tissues (eyestalk ganglia, brain and thoracic ganglia complex) and followed by midgut, the pericardial organ, abdominal muscle and the heart. As Cas-ILPBP contains a putative Ig domain, it is hypothesized that this protein may be involved in immunity, particularly in the adult females infected with a reo-like virus (CsRV1). The expression levels of Cas-ILPBP are examined in several tissues (hemocytes, midgut, eyestalk ganglia) from the animals carrying varying levels of CsRV1 at 17 and 23 °C water temperatures. Cas-ILPBP levels in the midgut are most significantly affected by high levels of CsRV1 infection. Reduction in Cas-ILPBP levels in the midguts is noted from the animals infected with high levels of CsRV1 that show reduced or stop feeding activity, indicating that it may play an important role in midgut functions such as digestion and nutrient absorption. Highlights: The full-length cDNA of an ILPBP ( Cas-ILPBP ) is isolated in C. sapidus. The putative sequence of Cas-ILPBP is closely related to other crustacean ILPBPs. The ubiquitous expression of Cas-ILPBP in the examined tissues is noted, with highest levels in the nervous tissues. Cas-ILPBP expression decreases significantly in midguts of the animals with high CsRV1 levels. Cas-ILPBP in the midgut may be involved in functions related to feeding, i.e., nutrient absorption.